2020
DOI: 10.1016/j.heliyon.2020.e04637
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of diesel engine injector nozzle spray characteristics fueled with residual fuel oil

Abstract: Experimental analysis on the spray characteristics of a diesel engine injector nozzle fueled with Residual Fuel Oil (RFO) was carried out in this study. To achieve this, the fuel was characterized to determine its physicochemical properties, and an experimental set up was designed to visualize and capture the spray pattern of the fuel. The images obtained were processed and analysed using Image J software to determine the spray length, spray cone angle, spray area, spray volume, and spray velocity values of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…Analysis of the literature [57,58] showed that the pressure of a mixture of liquid and air in the mixing chamber of the nozzle is a determining factor (excess air pressure contributes to the reverse flow of the liquid through the fuel path), affecting the jet characteristics after spraying. Thus, the pressure of the fuel and the spraying agent differed by 0.02 MPa.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Analysis of the literature [57,58] showed that the pressure of a mixture of liquid and air in the mixing chamber of the nozzle is a determining factor (excess air pressure contributes to the reverse flow of the liquid through the fuel path), affecting the jet characteristics after spraying. Thus, the pressure of the fuel and the spraying agent differed by 0.02 MPa.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Teknologi mesin pembakaran internal seperti mesin diesel banyak dipilih dalam aplikasi peralatan dengan tugas yang berat karena penghematan bahan bakar, ketangguhan, dan keandalannya [1]. Pada Gambar 1 merupakan salah satu contoh penggunaan mesin diesel pada alat berat forklift dengan merek komatsu tipe 8 ton yang banyak digunakan di industri kilang minyak [2].…”
Section: Pendahuluanunclassified
“…The fuel injection system has four functions. They put fuel into the injector, adjust the quantity of fuel, set the injection timing, and spray the fuel [2,3,4].…”
Section: Introductionmentioning
confidence: 99%